Pengaruh Dewan Komisaris Independen, Dewan Direksi dan Ukuran Perusahaan Terhadap Nilai Perusahaan dengan Corporate Social Responsibility sebagai Variabel Moderas Pada Perusahaan Makanan & Minuman yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2019-2023 - Permatasari, Intan; Lasmana, Andy; Anwar, Saepul (Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to analyze the influence of the Independent Board of Commissioners, Board of Directors, and Company Size on Company Value, with Corporate Social Responsibility as a moderating variable, in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. The study population included 94 food and beverage companies listed on the IDX during the period. The research sample was selected using a purposive sampling technique, resulting in 12 companies that met certain criteria. The method used in this study is Moderated Regression Analysis (MRA) with the help of Eviews software. The results of the study indicate that partially, the Board of Directors has an effect on Company Value, while the Independent Board of Commissioners and Company Size have no effect. However, simultaneously, the three variables contribute positively and significantly to the Value of food and beverage companies listed on the IDX for the period 2019-2023. In addition, Corporate Social Responsibility as a moderating variable strengthens the influence of the Independent Board of Commissioners and Board of Directors on Company Value, while company size has no influence on company value with corporate social responsibility as a moderating variable.